Water preconditioning on germination and emergence of Capsicum chinense Jacq. - Hernández López, Alejandro; Beltrán-Peña, Elda Guadalupe; Amancio-Oliveira, Antonia Elenir; Nuñez-Gaona, Oscar; Avila Alejandre, Alma Xochil (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this work was to determine the effect of water pre-conditioning on the percentage of germination and emergence of Capsicum chinense. The seeds were cultivated during the productive cycle from December 2015 to February 2016. For the pre-conditioning, the seeds were imbibed with 2.5, 3.5, 5, 7.5 and 10 ml of water. The volume of 7.5 ml was used as a reference. Germination results indicate that the three best imbibition volumes were 2.5, 3.5 and 5 mL, with a Pearson correlation of -0.905 (p= 0.000) between the volume of water and the percentage of accumulated germination, as well as the decrease of the germination time 50. Subsequently, the same seeds were transplanted to evaluate the emergence. The best imbibition volumes for the emergency were, in that order, 3.5, 5 and 2.5 ml. In the emergency, the volume with the best percentage of germination (2.5 ml) occupied the third place, which modified the Pearson coefficient to -0.641 (p= 0.01). The results suggest that a certain degree of stress, generated by the decrease in water supply, favors germination and establishment, which could be related to the synthesis and accumulation of ethylene within the germination system. On the other hand, the increase in the diameter of the water film generates a decrease in the availability of oxygen. The contribution of the present work was to demonstrate that the correct hydration of the seeds influences later stages of germination, without adding growth regulators.
Keywords: Capsicum chinense; Capsicum chinensez; germination